Equity-based career development and postsecondary transitions : an American imperative - Hines, Erik M.; Owen, Laura (Contemporary perspectives on access, equity and achievement., 2022)
"Former First Lady, Michelle Obama believes that every individual should have some type postsecondary education or training beyond high school to achieve economic and personal success (Reach Higher Initiative, Make Better Room, 2019). Educational attainment (e.g., a high school diploma, college degree, or postsecondary training) provides career opportunities for advancement into leadership positions and benefits such as health insurance and retirement (Heckman, 2000). Additionally, an individual with a college degree can make over one million dollars more over a lifetime in salary than someone with a high school diploma (Carnevale, Cheah, & Hanson, 2015). Acquiring a college degree can lead to employment opportunities and is considered an asset in the U.S. economy (Washington, 2010). However, certain populations encounter barriers to attaining an education, particularly a postsecondary education, leading to a disparity in receiving the aforementioned benefits. Some of these populations include African American students, LGBTQ students, and students with disabilities. There is a dearth of information and research on providing guidance on implementation, research, and best practices in equity-based career development, college readiness, and successful postsecondary transitions for minoritized, at risk, or vulnerable populations. The editors of this volume intend to invite authors with research and practice expertise around various student populations in preparing them for college and career readiness as well as postsecondary transitions. This book will be the first of its kind to discuss career development and postsecondary transitions from an access and equity perspective. Further, this text serves as a call to action to ensure the United States's most vulnerable populations has an opportunity to successfully transition into multiple postsecondary options after high school"--